2010
DOI: 10.1111/j.1756-185x.2010.01577.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in young males with ankylosing spondylitis

Abstract: OP is a significant complication in AS even in young males with early disease, and more prevalent in the spine compared to femur. In our study, BMD was not influenced by disease activity indices, inflammatory markers or total disease duration. Spinal BMD is the most sensitive site for defining OP in AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 17 publications
(30 reference statements)
1
25
0
Order By: Relevance
“…In a radiographic study, osteoporosis was detected in more than half of the patients with AS (5). The frequency of osteoporosis in AS was 18.7% to 62% in other similar studies (6-8). Bone loss is common in patients with long duration of AS; however, the prevalence of decreased bone mineral density (BMD) in patients with short disease duration is also high (9).…”
Section: Introductionsupporting
confidence: 52%
“…In a radiographic study, osteoporosis was detected in more than half of the patients with AS (5). The frequency of osteoporosis in AS was 18.7% to 62% in other similar studies (6-8). Bone loss is common in patients with long duration of AS; however, the prevalence of decreased bone mineral density (BMD) in patients with short disease duration is also high (9).…”
Section: Introductionsupporting
confidence: 52%
“…Moreover, the majority of the studies found a positive correlation between BMD and disease duration with AP/PA projection of the spine while no correlation was found with the lateral projection or at hip. However, most of the studies did not observe correlation with AP/PA projection of the spine or at hip 135 141 146–148 151 158–160. In patients with PsA, published data are scarce.…”
Section: Resultsmentioning
confidence: 99%
“…In axSpA, 20 studies compared DXA at different sites for distinguishing between patients with AS and controls. Fifteen of these studies compared the AP/posterior–anterior (PA) projection at the spine versus the hip region but the results were inconsistent: six studies observed no differences,136 139–143 eight reported results in favour of the hip135 144–150 and one in favour of the spine 151. Three studies compared the AP/PA versus the lateral projection at the spine and all reported that the lateral projection differentiated better between AS and controls 145 146 149.…”
Section: Resultsmentioning
confidence: 99%
“…Radiographic progression, such as syndesmophyte formation and vertebral bridging, is associated with a reduction in spinal flexibility. This increased rigidity means that a simple fall or other minor trauma can result in VFs [18]. Another explanation for the increased risk of VFs in AS is low bone mineral density (BMD).…”
Section: Discussionmentioning
confidence: 99%